Analisis Fundamental Perusahaan Pada Harga Saham Perusahaan Industri Barang Konsumsi Di Bursa Efek Indonesia - Dian Safitri Koesoemasari; Windarti Setiani; Harsuti Harsuti; Endang Sri Wahyuningsih (Majalah Imiah Manajemen & Bisnis, 2022)
This study aims to determine the significance of the effect of net profit margin, current ratio, debt to equity ratio and dividend payout ratio on stock prices in consumer goods industry companies listed on the Indonesia Stock Exchange. The samples obtained were as many as 8 companies using the purposive sampling method. The analysis technique used is the panel data analysis technique. The results showed that net profit margin, current ratio, debt to equity ratio and dividend payout ratio had a significant effect on stock prices. The implications of this study for potential investors to pay attention and consider the ratio of NPM, CR, DER and DPR because the ratio proved significant to strengthen the rise and fall of stock prices. An additional finding in this study is that CR has a significant negative effect, meaning that the condition of a company that is too liquid can result in a decrease in profitability for the company. Investors need to pay attention to the CR of a company in assessing the company's shares, so it is not wrong to choose the company to buy its shares.